KEARIFAN LOKAL DALAM PERSPEKTIF BUDAYA BANJAR - Wahyu Wahyu (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Local wisdom belongs to the local community. This local wisdom is lived, practiced, taught and passed on from one generation to another which at the same time forms the pattern of everyday human behavior, both towards fellow humans and towards nature. Local wisdom is noble values ​​that are believed to be true, apply in the life order of local communities and aim to protect and manage the environment in a sustainable manner. South Kalimantan is one of the cities that has diverse local wisdom, both local wisdom that has been there for a long time passed down from generation to generation as well as local wisdom that has just emerged as a result of interaction with other communities and cultures. The current paradigm of modern science and technology has affected the loss of some of the values ​​of local wisdom. Therefore, efforts to explore, discover, build and preserve the values ​​of local wisdom become a necessity.